Hubungan Stress Akademik dengan Pembelian Impulsif Mahasiswa/i (Studi Korelatif pada Mahasiswa/i Prodi Bimbingan & Konseling Universitas Sanata Dharma Angkatan 2022) - Agnes Lisa Dora S; Bernardinus Agus Arswimba (Journal of Counseling and Humanistic Studies, 2026)
This research aims to determine the relationship between academic stress and impulsive buying behavior among students of the Guidance and Counseling Study Program at Sanata Dharma University, Class of 2022. The study employed a quantitative correlational research design and involved 132 respondents selected through total sampling. Data were collected using two instruments: the Academic Stress Scale (50 valid items; Cronbach’s Alpha = 0.904) and the Impulsive Buying Scale (22 valid items; Cronbach’s Alpha = 0.927). The results of the Spearman’s rho correlation test indicate a significant positive relationship between academic stress and impulsive buying, with r = 0.145 and p = 0.049. These findings suggest that the higher the level of academic stress, the greater the tendency for students to engage in impulsive buying, although the relationship is categorized as very weak. Additionally, most students were classified within the moderate level of academic stress (48%) and low level of impulsive buying (30%). Therefore, academic stress has a significant positive influence on impulsive buying behavior among Guidance and Counseling students at Sanata Dharma University, Class of 2022.